Comparative optimization study for chemical synthesis of hydroxypropyl starch from native corn and taro starch through evolutionary operation (EVOP) factorial design technique. Issue 1 (9th October 2014) - Chattopadhyay, Jayati; Banerjee, Soumitra; Bhattacharyya, A. K.; Tester, Richard F.
<x xml:space="preserve">Abstract</x> Modification of native starch is aimed at tailor‐making functional properties of starch to overcome its inherent shortcomings which will enhance its versatility for different food‐uses. Optimization of chemical synthesis of hydroxypropyl starch from two native starch sources, corn and taro, was explored through application of evolutionary operation (EVOP) factorial design technique. Concentrations of starch slurry, propylene oxide, and sodium sulfate were considered as process variables and these were optimized in order to maximize swelling power of hydroxypropyl starch. EVOP factorial designing technique was applied consecutively and the results were analyzed statistically. Maximization of swelling power was achieved by corn starch after two sets of experiments of EVOP and the maximum value obtained was 36.17 at 20% sodium sulfate, 50% starch slurry, and 3.2% propylene oxide concentrations. The highest value of swelling power for hydroxypropyl taro starch was measured to be 62.33 after two sets of experiments and there was still scope for increasing its value in further set of experiments. Final conditions for taro starch were found to be optimum at 30% sodium sulfate, 40% starch slurry, and 5.6% propylene oxide concentrations, evaluated through EVOP method.